Yield responses of forage sorghums to salinity and irrigation frequency - Hassan, Siti Aishah; Saberi, Alireza; Abd Halim, Mohd Ridzwan; Abdul Rahman, Zaharah (Academic Journals, 2011)
Water stress restricts crop yield in both the arid and semi-arid zones of the world. In particular, water stress is associated with low availability of water, as well as osmotic effects associated with salinity. The response of forage sorghum [Sorghum bicolor (L.) Moench] varieties to salinity and irrigation frequency were studied from December 2007 to December 2008. Speedfeed and KFS4 were grown under salinity levels of 0, 5, 10 and 15 dS m-1 and irrigated when the leaf water potential reached -1.0 (control), -1.5 and -2.0 MPa. The irrigation frequency was found to affect growth and yield of the forage sorghums. When irrigation was delayed in leaf water potential of -1.0 to -2.0 MPa, the yield and yield components were found to decrease. The maximum dry forage yields were 45.1, 38.9 and 38.5 g plant-1 for frequent, intermediate and infrequent irrigation regimes, respectively. Increased salinity significantly reduced forage dry yield from 44.09 g plant-1 in the control to 32.76 g plant-1 at salinity of 15 dS m-1. For every one unit increase in salinity, the forage yield decreased by 5.2 units and for every one unit increase in water stress (irrigation frequency), the forage yield decreased by 3.6 units. The variety Speedfeed had higher total dry mass than KFS4 under well-watered conditions but KFS4 performed better than Speedfeed under water stress. For both varieties, infrequent watering reduced dry matter and biomass accumulation, but increased water use efficiency (WUEs) (6.88).